Meta-Analysis of Butyric Acid: a Performance-Enhancing Additive to Replace Antibiotics for Broiler Chickens - Giacomini, P. V. [UNESP]; Braga, F. S.C. [UNESP]; Araujo, R. G.A.C. [UNESP]; Cruz-Polycarpo, V. C. [UNESP]; Polycarpo, Gustavo Do Valle [UNESP] (FapUNIFESP (SciELO), 2022)
Butyric acid has been studied and utilized intensively in broiler chicken production in order to substitute growth-promoting antibiotics. However, the comprehensive literature on this topic makes it difficult to understand overall results, since there is a noticeable number of studies with conflicting conclusions. Although several research studies have shown that butyric acid may increment broiler chicken’s performance, several other studies show the opposite. This work aimed to organize information to understand, through a meta-analysis, whether butyric acid can be used as a performance-enhancing additive for broiler chickens, and whether it can replace growth-promoting antibiotics. It was clear from the results that the effect of butyric acid depends on the microbiological challenge that broilers receive. When broilers are raised without health challenge, butyric acid and even antibiotics do not influence growth performance. However, when broilers are challenged, butyric acid provided an increase in weight gain and a significant improvement in feed conversion, matching the results of antibiotics. We conclude that butyric acid improves broiler performance and can be used to replace growth-promoting antibiotics.
Keywords: Butyric acid; feed additive; growth-promoting antibiotic; organic acid; performance; systematic review